The Effectiveness of Task Based Intruction (TBI) toward Students’ Interest in Learning English Vocabulary at SMPN 1 Sambelia - Sudirman Sudirman; Tawali Tawali (JUPE : Jurnal Pendidikan Mandala, 2022)
This research was aimed at find out whether or not using Task Based Intructionhas positive effect toward students’ interest in learning English vocabulary. Thisresearch was an experimental research.The population the second year students of SMPN 1 Sambelia in academic year 2021/2022 was 209 students. The sample of the research was 54 students. The sample was taken by cluster random sampling technique. The instrument that was used test (20 items) and questionnaire. The score were analyzed by used descriptive and inferential analysis. Descriptive analysis was used to describe mean, mode, median, and standard deviation of group according to AnasSudijono:2007, and inferential analysis was used to describe the value of t-test for comparison between t-table. It was showed that the value of-test = 2.575 was higher than the value of t-table = 1.675. So, using Task Based Intruction approach has positive effect toward students’ interest in learning English vocabulary at SMPN 1 Sambelia.